2017
DOI: 10.1186/s12861-017-0149-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two related lines of tauGFP transgenic mice designed for lineage tracing

Abstract: BackgroundThe tauGFP reporter fusion protein is produced nearly ubiquitously by the TgTP6.3 transgene in TP6.3 mice and its localisation to microtubules offers some advantages over soluble GFP as a lineage marker. However, TgTP6.3 Tg/Tg homozygotes are not viable and TgTP6.3 Tg/− hemizygotes are smaller than wild-type. TP6.4 mice carry the TgTP6.4 transgene, which was produced with the same construct used to generate TgTP6.3, so we investigated whether TgTP6.4 had any advantages over TgTP6.3.ResultsAlthough Tg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…5F and Supplementary Video 1). This is very similar to the tau-GFP expression reported in this developmental stage [31]. Collectively, these data demonstrated that various thick organs can be cleared with the FxClear protocol, despite the concerns about limited tissue transparency and potential loss of proteins.…”
Section: Resultssupporting
confidence: 84%
“…5F and Supplementary Video 1). This is very similar to the tau-GFP expression reported in this developmental stage [31]. Collectively, these data demonstrated that various thick organs can be cleared with the FxClear protocol, despite the concerns about limited tissue transparency and potential loss of proteins.…”
Section: Resultssupporting
confidence: 84%
“…The tauGFP marker labelled the partner (BF1×TP6.3) embryos rather than the BALB/c embryos in series 4U chimaeras, or the AAF2 embryos in series 4B chimaeras. To allow all the chimaeric blastocysts to be analysed at equivalent stages, they were cultured in an environmental chamber on the stage of a confocal microscope ( Sharp et al, 2017 ) and imaged at intervals ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the experiments with GFP blastocyst chimaeras, embryos were aggregated, cultured in KSOM medium ( Summers et al, 1995 ) under mineral oil in an incubator (37°C, 5% CO 2 in air) for 24 h, then transferred to fresh pre-equilibrated drops of culture medium under mineral oil in a WillCo HBSt-3522, thin glass-bottomed dish (Intracel Ltd., Royston, Herts, UK). This was placed in an environmental chamber on top of the pre-heated stage (THD 60, Linkam Scientific Instruments Ltd., Tadworth, UK) of a Leica DMIRB/E inverted confocal microscope, and the atmosphere within the chamber was maintained at 37°C, 5% CO 2 in air, as described elsewhere ( Sharp et al, 2017 ). Time-lapse images were acquired using the Leica TCS NT confocal system, and images from fluorescein isothiocyanate (FITC) and transmitted light channels were merged ( Sharp et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation